The Influence of Promotion and Store Image on Purchasing Decisions at Daryanto Store - Prihartono, Prihartono (Dinasti Publisher, 2023)
This study discusses Promotion and Store Image on Purchasing Decisions at Daryanto Store. The purpose of this study is to determine the impact of promotion and store image owned by Daryanto Store on purchasing decisions. The research method used is quantitative. The population in this study was 20 0 respondents with a sample of 90 respondents. The sampling technique is simple random sampling. Data is obtained from questionnaires sent to consumers from the store via email to be filled out. The research conducted is Test T, Test F and coefficient of determination. The results of this study include: 1) Promotion affects Purchase Decisions at Daryanto Store partially, where with good promotions will make consumers confident to make purchase decisions; 2) Store Image affects Purchase Decisions at Daryanto Store partially, where with a good store image it convinces consumers to make purchasing decisions at the daryanto store; and 3) Promotion and Store Image influence the Purchase Decision at Daryanto Store simultaneously.